Implementation of Character Education Through Coaching Discipline of Students - Windu Widagdo; Nurdyansyah Nurdyansyah; Yayuk Faujiyah (International Consortium of Education and Culture Research Studies, 2020)
The qualitatif research about implementation of education has been applied through discipline coaching of students at SMP Muhammadiyah 1 Sidoarjo on December 2nd until 4th, 2019. This research objective is the implementation on character education of discipline coaching of students at Muhammadiyah 1 Junior High School Sidoarjo. The research method is qualitative research. The result of this research are: (1) discipline coaching management are divided into two strategies, which are internal coaching and external coaching, (2) discipline coaching school strategy can be applied through extraculicular activities, spiritual activities, habitual activities, uniform and attributes allowed, rules of time to come and leave the school, the lateness of the students, manner in school relationship, clean and order, following flag and celebration ceremony, and (3) external coaching strategy through parents and society cooperation, (4) the percentage of students lateness was 10% descend, the percentage of inappropriate uniform was 23% descend, also the percentage of students absence without permission was 88% descend at education year 2018/2019.